Variability in summer anticyclonic circulation over the Canadian Arctic Archipelago and west Greenland in the late 20th/early 21st centuries and its effect on glacier mass balance. (7th April 2014) - Bezeau, P.; Sharp, M.; Gascon, G.
ABSTRACT: More frequent summer anticyclonic circulation over the Canadian Arctic Archipelago (CAA) between 2007 and 2012 caused more intense and sustained melt of ice caps and glaciers and increased rates of mass loss. To determine the frequency of the occurrence of anticyclonic circulation over the CAA and western Greenland, a self‐organizing map (SOM) was used to classify daily 500 hPa geopotential height (GPH) anomalies calculated from National Centers for Environmental Prediction and the National Center for Atmospheric Research (NCEP/NCAR) Reanalysis 1 (1948–2012) and five Coupled Model Intercomparison Project Phase 5 (CMIP5) models (1950–2025). While the NCEP/NCAR reanalysis indicates that significant summer warming over the CAA is linked to a doubling in the frequency of anticyclonic circulation over the region since 2007, the CMIP5 models were not capable of reproducing the magnitude of the trend in the frequency of anticyclonic circulation over the CAA and western Greenland found in NCEP/NCAR. The variability of the frequency of positive anomalies in summer 500 hPa GPH was found to be related to variability of Arctic sea ice volume/thickness in April, May and June (1979–2012) and to poleward eddy heat flux in June (1979–2012).